An In‐Depth Study of Regulable Zincophilic Alloy Matrix toward Stable Zinc Metal Batteries. Issue 7 (28th January 2022) - Zhao, Qiwen; Wang, Yunyun; Liu, Wen; Liu, Xiaoyu; Wang, Han; Yu, Huaming; Chen, Yuejiao; Chen, Libao
Abstract: Introducing 3D hosts is recognized as valid means to low the local current density for alleviating dendrite problems. However, the uncontrollable "top growth" behavior on some 3D hosts is still a serious issue. Although some strategies on the manipulation of Zn 2+ ion flux by causing Zn‐alloying metals are reported, the covert details during cycles are still ignored. A tuned Cu‐Zn alloy interfacial layer on stainless‐steel mesh (SS) is proposed here as a fresh tactic. The zincophilic scaffold furnishes nucleation sites and lowers energy barriers for axipetally controllable Zn plating. In‐depth study reveals that Cu x Zn y phase generated by variable Cu/Zn ratios preferentially forms into CuZn5 with Zn plating and then converts into metallic Zn in plating cycle, and no decomposition in a given voltage range in stripping process due to a negative Gibbs free energy of formation of zinc alloys. Thus, CuZn5 is the main zincophilic seed in the subsequent cycles, regardless of any Cu x Zn y phases. As a result, the optimized SS in Zn//MnO2 full cell can render 70% retention after 350 cycles, while the bare SS only shows retention of 30%. Abstract : A tuned Cu‐Zn alloy interfacial layer coated on stainless‐steel mesh furnishes abundant nucleation sites and lowers energy barriers for axipetally controllable Zn plating. The CuxZny phase generated by variable Cu/Zn ratios preferentially transforms into CuZn5 with Zn plating. A general and effective avenue via synergistic combination of general skeletons with zincophilic alloy sites is provided to stabilize Zn cycling.